Degradação de materiais poliméricos : estudos de casos de falha em faróis de policarbonato e fotodegradação de revestimentos de poli(tereftalato de etileno) em aço carbono - Mônica Martiniano Ferreira (2020)
In order to achieve the desired performance by the automobile industry in the use of new materials, it is necessary to master the properties and behavior of the material under the most severe conditions of use, and thus reducing the probability and frequency of unexpected failures. Polymeric materials are highlighted in the replacement of conventional materials due to their characteristics of low density, processability and mechanical response, among others. Despite this, its high vulnerability in certain conditions can lead to serious damage, restricting its use. In this sense, product performance tests can identify failures and their causes. The present work addresses two conditions for evaluating the product in different phases. The first study refers to the failure of rupture in automotive headlights during use, that is, at the stage when the component is already consolidated in the market. The study pointed out that cracks are caused by one or more mechanisms: creep, thermal stress, and Environmental Stress Cracking (ESC), caused by the stress relief of the polymeric material of the lens. The probability of failures is mitigated when the development of the project considers the extreme and degrading conditions to which the product will be subjected. In this case, the conception of a design that accommodates the lens at an adequate distance from the light source, and / or the use of a material with a greater mechanical and thermal resistance, are minimal premises that would considerably reduce the chance of design failures. The second case is the study of the degradation behavior of an anti-corrosion polymeric coating, made of PET bottles, still in the development phase. The two main degradation mechanisms were the photolysis and photo oxidation of PET, in addition to the synergistic effect of both. It was also evidenced the need to implement strategies to adapt the polymeric material as an anti-corrosion coating of carbon steel sheets, for weathering applications, such as the insertion of stabilizers and ultraviolet radiation absorbers, which combine good protection and low cost.